2012
DOI: 10.5296/ijafr.v2i1.1825
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of capital structure decisions with firm performance: A study of the engineering sector of Pakistan

Abstract: Purpose: The purpose of this study is to find the relationship of capital structure decision with the performance of the firms in the developing market economies like Pakistan.Methodology: Pooled Ordinary Least Square regression was applied to 36 engineering sector firms in Pakistani market listed on the Karachi Stock Exchange (KSE) during the period 2003-2009.Findings: The results show that financial leverage measured by short term debt to total assets (STDTA) and total debt to total assets (TDTA) has a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
86
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 32 publications
(30 reference statements)
18
86
2
9
Order By: Relevance
“…In a study, Abor (2007) found a positive relationship between short term debt and return on assets in small and medium enterprises (SMEs) because of the nature of industry in which they are operating and low level of interest rates. These finding are not consistent with the study by Khan (2012) that financial leverage measured by short term debt to total assets (STDTA) has a significant negative relationship but has consistency with the result that total debt to total assets (TDTA) with the firm performance measured by Return on Assets (ROA) has significant negative relationship. The independent variables are moderately related with ROA since the value of Adjusted R-square is 0.603.…”
Section: From the Pearson Correlation Matrix (contrasting
confidence: 89%
“…In a study, Abor (2007) found a positive relationship between short term debt and return on assets in small and medium enterprises (SMEs) because of the nature of industry in which they are operating and low level of interest rates. These finding are not consistent with the study by Khan (2012) that financial leverage measured by short term debt to total assets (STDTA) has a significant negative relationship but has consistency with the result that total debt to total assets (TDTA) with the firm performance measured by Return on Assets (ROA) has significant negative relationship. The independent variables are moderately related with ROA since the value of Adjusted R-square is 0.603.…”
Section: From the Pearson Correlation Matrix (contrasting
confidence: 89%
“…The insignificant relationship between the STDR and accounting based measure which is ROA indicates that STDR has no significant impact on returns of construction firms in Malaysia. This result is consistent with the study by Ebrati, Emadi, Balasang, and Safari (2013), Hamid, Abdullah, and, Kamaruzzaman (2015), Hasan, Ahsan, Rahaman, and Alam (2014), Khan (2012), Olokoyo (2013), andTaani (2013). Table 2 also shows that the relationship between LTDR and ROA in construction firms in Malaysia is not statistically significant (LTDR: β = -1.6402, p > 0.05).…”
Section: Capital Structure and Return On Assetsupporting
confidence: 90%
“…Among the financial ratio, ROA is found to be the most popular and useful financial ratio. ROA can be derived by dividing net income plus interest expenses with total assets (Ebrati et al, 2013;Khan, 2012). The ratio was introduced by DuPont company back in 1919 where they used it as the top of their ratio triangle system (Jewell & Mankin, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Abor (2005) proved that due to the large percentage of short-term financing, profitability is positively related to debts because profitable company regards debts as the primary financing source (Khan 2012). Gill et al (2011) discovered that both long-term debts and short-term debts are positively correlated with profitability.…”
Section: Profitabilitymentioning
confidence: 99%